Temperature dependence of mechanical degradation in lead-free alkali niobate ceramics under unipolar loading - Martin, Alexander; Kakimoto, Ken-Ichi; Hatano, Keiichi; Doshida, Yutaka (Materials Letters, 2016)
Piezoelectric actuators are used under high electric fields, which can cause crack formation as a consequence, and therefore require sufficient mechanical properties to guarantee long lifetime and reliability. We measured the flexural strength before and after unipolar fatigue under different temperatures of undoped Li0.06Na0.52K0.42NbO3 (LNKN6) and the same compound with additives (LNKN6-A). Before performing fatigue tests, the flexural strength a sigma(0) was 111 MPa and 177 MPa for LNKN6 and LNKN6-A, respectively. After electric cycling over a certain amount of time, only slight changes in the piezoelectric properties were observed. However, mechanical degradation appeared in LNKN6 whereas LNKN6-A remained the as-poled flexural strength throughout each test. The results suggest that a smaller grain size is an advantage in case of crack formation during unipolar fatigue. In addition, LNKN6 showed after cycling a bimodal Weibull distribution. Under room temperature, the highest mechanical degradation of about 35% was observed. Noteworthy is the fact that after 50 degrees C, less mechanical degradation was observed. It is suggested, that phase transition from tetragonal to orthorhombic lead to improved mechanical properties. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Actuators; Fatigue; Flexural strength; Lead-free; Phase transformation